Challenges of Implementing the Independent Curriculum in Islamic Religious Education Learning at SMP Negeri 24 Medan - Romdhoni, Muhammad Ali; Hasibuan, Hilman Rizky; Basri, Hasan (TARBAWY: Indonesian Journal of Islamic Education, 2023)
This study aims to find out how the implementation of the independent learning curriculum, find out the problems faced in the implementation of the independent learning curriculum, and find out how the form of assessment of Islamic religious education learning based on the independent curriculum at SMP Negeri 24 Medan. This research is a field research using descriptive qualitative method. Collecting data in this study using interviews, observation and documentation. The results of the research showed that the learning of Islamic religious education in the independent learning curriculum at SMP Negeri 24 Medan was fully handed over to teachers and students. Teachers are given freedom in making lesson plans, such as using strategies, methods, media and learning approaches. The problems of learning Islamic religious education in the independent learning curriculum are: teachers still have difficulties in developing independent learning-based learning, incomplete facilities, teachers are comfortable with the 2013 curriculum and inadequate human resources. While the teacher's strategy in implementing the curriculum, namely: formulating learning objectives, determining teaching and learning activities, determining tools and materials for learning, planning the evaluation of Islamic religious education learning.